Sedentary Lifestyle and Nonspecific Low Back Pain in Medical Personnel in North-East Poland. (9th September 2018) - Citko, Anna; Górski, Stanisław; Marcinowicz, Ludmiła; Górska, Anna
Abstract : Introduction . The sedentary lifestyle is defined as prolonged sitting both at work and during leisure time, with energy expenditures of below 600 MET · min/week. The sedentary lifestyle is a well-known predictor of obesity and other components of the metabolic syndrome. The influence of the sedentary lifestyle and associated factors on nsLBP is still being discussed. Aim . The aim of this study was to assess the influence of a sedentary lifestyle and its associated metabolic predictors on the prevalence of nsLBP in nurses and paramedics. Materials and Methods . The study included 609 participants, aged 30-60 years, who were residents of north-east Poland. Data was collected using a questionnaire (based, in part, on the Nordic Musculoskeletal Questionnaire), and included details of sociodemographic profile, chronic illnesses, and a short version of the International Physical Activity Questionnaire (IPAQ). Results . Nearly half (49.59%) of the respondents reported decreased physical activity, and in the group with recurring nsLBP this figure was 67.59%. Univariate logistic regression modelling found that leading a sedentary lifestyle caused a 3.5-fold increase in the incidence of recurring nsLBP (p<0.001). Excessive coffee consumption significantly increased the likelihood of recurring LBP (OR=16.44, 95% CI: 8.55-31.61), and cigarette smoking increased the likelihood of both recurrent and chronic LBP. The likelihood of chronic low back pain was significantly increased by components of metabolic syndrome such as high blood pressure (over 9-fold), type 2 diabetes (over 3-fold), and hyperlipidemia (over 2-fold) (p<0.001, p<0.001, and p<0.01, respectively). Conclusions . A sedentary lifestyle significantly increased the incidence of recurring low back pain, while increased physical activity had a significant effect on the presence of chronic low back pain. In the sedentary lifestyle group, conditions classified within metabolic syndrome were found to significantly increase the chances of developing nonspecific low back pain.